Gender difference in betel quid consumption levels and tobacco use among adults in Myanmar - Yin Min Aye; Seo Ah Hong; Bang-On Thepthien; Sariyamon Tiraphat (International Journal of Public Health Science (IJPHS), 2021)
Several small scaled studies in Myanmar investigated determinants of betel quid chewing status but to better understand more complete profiles of betel quid chewing habits, this study investigated the associations of betel quid consumption levels with tobacco and sociodemographic factors using a nationally representative sample in Myanmar. A cross-sectional, secondary data analysis was conducted by using Myanmar demographic and health survey (MDHS) (2015-2016). Chi-square tests and multinomial logistic regression were performed with p-value<0.05 as significance. Men averagely chewed 5.59 (SD=8.229) pieces per day while women chewed 1.25 (SD=3.584) pieces. The prevalence of chewing daily pieces 1-2, 3-5 and 6+ were 7.9%, 17.1% and 34.2% for men and 6.1%, 8% and 7.1 %, respectively, for women. In multivariate analysis, low education, low family wealth, married, and urban were more likely to chew 6+ pieces per day relevant to no consumption in both genders, while a positive association with age was observed only in women. Tobacco use was associated with low consumption level (1-2 pieces), relative to no consumption in both genders. Therefore, this study underlined the need to improve knowledge on the dangers associated with betel quid chewing and tobacco use among socially disadvantaged populations and urban residents.